2009
DOI: 10.1073/pnas.0903227106
|View full text |Cite
|
Sign up to set email alerts
|

A thyroid hormone receptor mutation that dissociates thyroid hormone regulation of gene expression in vivo

Abstract: Resistance to thyroid hormone (RTH) is most often due to point mutations in the ␤-isoform of the thyroid hormone (TH) receptor (TR-␤). The majority of mutations involve the ligand-binding domain, where they block TH binding and receptor function on both stimulatory and inhibitory TH response elements. In contrast, a few mutations in the ligand-binding domain are reported to maintain TH binding and yet cause RTH in certain tissues. We introduced one such naturally occurring human RTH mutation (R429Q) into the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 76 publications
3
48
0
2
Order By: Relevance
“…7B). There were relatively fewer T3-down-regulated genes that had both TR␤1 and RXR␣ ChIP peaks (41% for TR␤1-PTU ChIP peaks), which is in agreement with an earlier report that demonstrated that TR homodimers might be more important for negative regulation (35). These FIGURE 6.…”
Section: Validation Of Binding Sites and Gene Expression Determined Bsupporting
confidence: 79%
“…7B). There were relatively fewer T3-down-regulated genes that had both TR␤1 and RXR␣ ChIP peaks (41% for TR␤1-PTU ChIP peaks), which is in agreement with an earlier report that demonstrated that TR homodimers might be more important for negative regulation (35). These FIGURE 6.…”
Section: Validation Of Binding Sites and Gene Expression Determined Bsupporting
confidence: 79%
“…2). On the Gh gene, THR is bound to a Ϫ220 bp site (28,29). NCOR1 was enriched in this region and released upon T 3 treatment, consistent with reports on Gh regulation (Fig.…”
Section: Resultssupporting
confidence: 77%
“…On some occasions, mut TRβs may show greater impairment of transactivation on genes negatively rather than positively regulated by T 3 [41,54]. Recent work suggests that the mut TRβ R429Q affects predominantly the TRβ2 mediated action [55] while mut TRβ R338W, through its association with a single nucleotide polymorphism in the enhancer region, produces over expression of the mut TRβ allele [56]. These two mechanisms give credence to the existence of predominantly pituitary RTH.…”
Section: Variants Above)mentioning
confidence: 99%